Development of rules for budget allocation and methods for evaluating media plans for the digital space - D. A. Khokhlov (Вестник университета)
The article studies methods of advertising campaign budget allocation in digital space using advertising hypotheses. The author proposes a new approach based on the use of advertising hypotheses as an advertising medium. A form of media plan specifically designed for digital space has been presented. Special attention is paid to two types of advertising campaigns: those that pay for clicks or impressions and those that use direct marketing tools (SMS, mobile notifications and email newsletters). A way to evaluate media plan effectiveness has been suggested. The author believes that the main task at the stage of media planning is to determine whether the developed advertising hypothesis is able to achieve the planned indicators. This approach can improve advertising campaigns effectiveness in digital space and ensure more accurate budget allocation. The results of the study can be useful for marketers and advertising agencies, helping them make informed decisions when planning and optimizing advertising campaigns in digital space.